Sagartia troglodytes (Anthozoa: Actiniaria) consists of two species - Shaw, P.; Beardmore, J.; Ryland, J. (Marine Ecology Progress Series, 1987)
The sagartiid sea anemone Sagartia troglodytes (Price) has usually been considered to consist of 2 morphological varieties hked by intermediate forms (and therefore presumably by interbreeding). The techniques of starch gel electrophoresis and chromosome preparation, combined with an analysis of reproductive biology, were employed to investigate populations around the SW coasts of Britain to test this assumption. Var. decorata is extremely variable both morphologically and genetically with high levels of polymorphism and heterozygosity (P = 61 %, H, = 0.27). It reproduces exclusively by out-crossing, oviparous means producing maximal genotypic diversity and good gene flow between populations (Nei's Genetic Identity, 1 = 0.99). Var. ornata is less variable morphologically but genetically diverse (P = 62 %, H. = 0.47) due to 'fixed heterozygosity' at some locl, which is maintained by extensive clonal reproduction within populations producing relatively low inter-population identity (f = 0.86). Var. decorata has a chromosonle number of approximately 24 whereas var. ornata has approximately 48. On this basis it is proposed that var.decorata should retain the species name S. troglodytes (Price) and that var. ornata be restored to species status as Sagartia ornata (Holdsworth, in Gosse 1860).